Pendampingan Produksi dan Kontrol Kualitas Olahan Telur di UKM Abinisa-Serang - Wulandari, Zakiah; Ulupi, Niken; Arief, Irma Isnafia; Aminah, Siti; Budiman, Cahyo; Adiansyah, Dias (Institut Pertanian Bogor, 2026)
Abinisa SME collaborates with duck farmers in Sujung Village to process eggs into salted eggs, egg rolls, egg powder, and salted egg sauce powder, which are marketed in Serang and the Greater Jakarta (Jabodetabek) area. The community service program at Abinisa SME aims to support business development and improve product quality through training, mentoring, and the provision of processing equipment. The training focused on duck feed management, food safety, product diversification, and digital marketing, while mentoring by MBKM students assisted in the practical implementation of the materials and helped address production challenges. The provision of new equipment facilitated hygienic and efficient production processes, allowing the benefits of the program to be directly realized. The evaluation, conducted using pre-tests, post-tests, and questionnaires, showed increased participant understanding, high motivation to apply the knowledge gained, and positive responses toward the mentoring activities and the use of the equipment. These evaluation results serve as a basis for future program improvements to ensure sustainable benefits for the development of Abinisa SME and its contribution to economic growth.